2005
DOI: 10.1097/01.mlr.0000156862.33341.45
|View full text |Cite
|
Sign up to set email alerts
|

Utilities For Prostate Cancer Health States in Men Aged 60 and Older

Abstract: Both "watchful waiting" and treatment complications from prostate cancer treatments can have large impacts on quality of life. Mean ratings are important for use in policy-making and cost-effectiveness analyses. Variation in ratings across patients suggests that mean scores do not reflect individual preferences and that shared decision-making may be best for clinical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 19 publications
4
127
0
2
Order By: Relevance
“…In an earlier study, Stewart et al [27] reported that bowel problem was rated as significantly more bothersome than impotence and urinary incontinence, and age was a significant predictor of higher utility ratings. In our study, we noticed most of the HRQoL subscales are associated with higher utility score, except for urinary function and sexual bother.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In an earlier study, Stewart et al [27] reported that bowel problem was rated as significantly more bothersome than impotence and urinary incontinence, and age was a significant predictor of higher utility ratings. In our study, we noticed most of the HRQoL subscales are associated with higher utility score, except for urinary function and sexual bother.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, QALY can be directly used in the cost-effectiveness analyses [9][10][11]. Thus, the utility scores represent the strength of an individual's preference for different health outcomes under conditions of uncertainty [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Which treatmentrelated symptom bears the greatest influence on post-treatment QOL? Utility analyses have shown that bowel symptoms have a greater negative impact on QOL than urinary symptoms or impotence (32). However, this may not apply for all patients, and shared decision making may be most appropriate (33).…”
Section: Discussionmentioning
confidence: 99%
“…Utilities measuring the quality of life during primary androgen deprivation therapy and watchful waiting with active surveillance were also used in the construction of the model. All values for utility were taken from Stewart et al [27]. Stewart et al obtained standard gamble utilities for 19 health states from 162 subjects recruited as volunteers from the San Diego, CA, area, 52% of whom had been diagnosed with prostate cancer.…”
Section: Estimating the Utility Of Health Statesmentioning
confidence: 99%